FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA SMP NEGERI 1 TALANG EMPAT KABUPATEN BENGKULU TENGAH TAHUN 2015 - Elvi Destariyani; Ratna Dewi (Universitas Jember, 2015)
Adolescent marked with the unbalance physical and mental growth whih is followed by behaviorally trying something into sex before marriage, they have earned. this avidence with persistence of students in SMPN 1 Talang Empat who do premarital sexual behavior deviations. Purpose of this study was to determinan the factors associated with adolescent premarital sexual behavior. This research uses with cross sectional method with the amount of samples taken by stratified random sampling technique were 105 responder consisting of students of class IX in SMPN 1 Talang Empat. Research was conducted on 22-30 january 2014, data retrieval using questionnaires and analysis of univariate, bivariate, and multivariate. At bivariate analysis found that have significant relations at knowledge ( =0,029), family envirovment =0,002), influence of peers ( =0,005), and media exposure ( =0,000) with adolescent premarital sexual bahavior. At multivariate analysis found that information media exposure variable is the most dominant factor influencing adolescent premarital sexual behavior with OR = 8,610. Advice to SMPN 1 Talang Empat besides imposing a ban on the students to bring mobile phones in schools, shuold also routinely conduct raids handphones (1-2times/month), and the teachers works together with parents in providing information and effective communication in adolescents especially with regard to sexual. Keyword: Knowledge, Family Environment, Influence of Peers, Premarital Sexual Behavior.